Networks in Aviation Strategies and Structures - Goedeking, Philipp; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Aviation networks play a critical role in the success of today$1 (Bs airlines and airports. This book provides insight on all aspects of modern network strategies and structures, ranging from market research to hub design, operations, organization, alliances, benchmarking, and antitrust issues. Considering both the airline and the airport perspectives, the book explains the economics of connectivity or productivity-driven hub structures through basic mathematics, which helps the reader to comprehend the structural strengths and weaknesses of aviation networks. More than 100 charts help clarify the topics at hand.s
Market Research: Overcoming Incomplete, Inconsistent, or Outdated Data -- Network Structures Follow Network Strategies -- Designing Connectivity-Driven Network and Hub Structures -- Designing Asset-Productive Networks -- Case Studies -- Planning and Controlling Networks: Networking Higher Math, Intuition, and Power Play -- Competition, Cooperation, Co-opetition, and Antitrust: Balancing Economies of Scale and Competitive Market Structures -- Multi-Hub Networks: Masterpieces or Nightmares of Complexity? -- Assessing and Comparing the Strengths and Weaknesses of Aviation Networks -- An Overarching Concept: The Hierarchical Layers of Aviation Networks.
Keywords: Economics; Astronautics; Engineering economy; Industrial management; Operations research; Business planning; Economics/Management Science; Management/Business for Professionals; Operation Research/Decision Theory; Aerospace Technology and Astronautics; Organization/Planning.; Engineering Economics, Organization, Logistics, Marketing